Dynamic control of vibrations during turning - Zaloha, V.; Shapoval, Ju.; Drofa, К.; Krivoruchko, D. (Mechanics and Advanced Technologies, 2017)
Abstract. Purpose. Identification the effects that lead to a decrease in the vibration amplitude during the dynamic control of the machine tool additional mass location and determination the limits of this method application. Design/methodology/approach. Study uses high spindle speed machine tool of special design. The experimental measurements of tool, carriage, spindle and base accelerations and displacements were carried out and compared to the results of finite element modal analysis. Tests concentrated on two structural variants of machine tool that differ with additional mass amount. Findings. The experimental results confirmed the possibility of decreasing of the relative tool edge vibration amplitude and roughness of the machined surface when changing the additional mass location in the machine tool system. Modal analysis showed that this effect results from the change in structure eigenform. Thus, the decrease in the amplitude of the relative tool edge displacement is possible by dynamic control of additional mass location with the aim of guaranty the tool edge location in the vibration node. This effect is easier to implement, the greater the spindle speed is used.